ClarisWorks 4.0 for the Macintosh SmartStart - Bitter, Gary G. (Que E&T, 1996)
Most aspects of ClarisWorks 4.0 contain improvements, and more than 100 new features are included. This new version is more powerful and easier to use, and some previously complex features have been simplified.